Preterm Prelabour Rupture of the Membrane & Feto-Maternal out come: an Observational Study - Akter, S; Akter, R; Rashid, M (Journal of Bangladesh College of Physicians and Surgeons, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: The aim of this study was to see the maternal and fetal outcome of preterm pre labor rupture membrane and to identify the risk factors for preterm pre labor rupture membrane. Methods and Material: This was a cross-sectional descriptive type study carried out in Dhaka Medical College Hospital, Dhaka, during April to September, 2005 (6months) in the Department of Obstetric and Gynecology. 50 pregnant women with preterm premature rupture of the membrane (gestational age 29-0 to 36-6 weeks) were included in this study. Results: The mean age of the women was 27.24±6.28years and 36% of them more than 30 years old. Sixty two percent women were multi gravid .Socio-economic condition, level of education and antenatal care of the women was low. Median gestational age of the patient was 35 weeks. Fifty six percent had previous history of PROM, preterm delivery, abortion, MR and dilatation and curettage. Sixty two percent women had history of sexual activity between 2 to 7days. Seventy two percent women had UTI, anaemia, and lower genital tract infection. Mean duration of the latent period was 18.87 ±16.17hours and time interval of rupture membrane and delivery was 27.60 ± 21.127 hours. Eighty four percent patient delivered by vaginal route and Fifty four percent delivered within 24 hours of ruptured membrane. Forty two percent newborn suffered from neonatal asphyxia, respiratory distress syndrome, neonatal jaundice and neonatal sepsis. Thirty two percent women suffered from chorioamnionitis, abruptio placent and endometritis. Conclusion: PPROM is malnutrition and poverty related disease. Antenatal care is an important tool to prevent PPROM by identifying the risk factors and its management. Steroid for fetal lung maturity, antibiotics to prevent fetal and maternal infection and induction and /or augmentation of labor will speeded delivery and reduce hospital stay and infection. Key words: Premature rupture of the membrane; maternal and neonatal outcome; risk factors. DOI: 10.3329/jbcps.v28i1.4639 J Bangladesh Coll Phys Surg 2010; 28: 17-23